VIKTIMISASI ANAK KORBAN PENYALAGUNAAN NARKOBA - Henky Fernando; Yuniar Galuh Larasati; Syahrul Akmal Latif (Ius Poenale, 2022)
The involvement of children in drug abuse cases not only positions children as victims but also creates victimization of children. This study not only describes the involvement of children in drug abuse but also explains the victimization of child victims. This study uses a qualitative descriptive. Data collection was collected by reading 2,000 online news texts using the search keyword "Keterlibatan Anak Dalam kasus penyalagunaan narkoba di Indonesia" on the Google search engine. The news text's reading focuses on the news's title, theme, and content from January 26 to February 2, 2022. From this reading, two dominant findings leads to the discussion in which  the victimization of child victims as a result as a result of drug abuse is essential  in this study. The analysis in this study is done by reducing, describing, and interpreting the data inductively to conclude. The findings in this study show that the child's involvement in drug abuse cases often positions children as drug users and traffickers. In this context, children as victims of drug abuse also get victimization by their friends, teachers, and school principals in the form of intimidation and discrimination.